Looking into the future (remnant liver) - Lodewick, Toine M.; Schaap, Frank G.; Olde Damink, Steven W.M. (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
The most common primary malignancy of the liver is hepatocellular carcinoma (HCC) (1). Approximately 80% of patients with HCC show chronic liver disease and cirrhosis. Chronic infection with hepatitis B or C virus, alcoholic liver disease and nonalcoholic steatohepatitis are the most frequent causes for developing liver cirrhosis (2). Other risk factors are hemochromatosis, primary biliary cirrhosis (PBC) and autoimmune hepatitis (3). Partial liver resection or liver transplantation remain the only potentially curative treatment options in patients with HCC. In recent years the indications for liver resection have been expanded due to improvements in surgical technique, perioperative care and chemotherapy regimens, leading to an increased number of patients that is now eligible for partial liver resection (4). This resulted in larger resections and consequently an increased risk of postresectional liver failure (PLF). PLF is the most important cause of death after partial liver resection (5,6). Between 0.7% and 9.1% of all patients undergoing partial liver resection develop this complication that is caused by insufficient remnant liver volume and function (5). Surgical treatment of patients with multifocal HCCs who do not meet the Milan criteria (one lesion smaller than 5 cm or a maximum of 3 lesions smaller than 3 cm in absence of vascular invasion and extrahepatic disease) is controversial, and in these cases transarterial chemoembolization is recommended (7). However, in patients with multifocal HCCs who do not meet the Milan criteria and complete resection of all tumours is not feasible, the combination of partial liver resection and radiofrequency ablation (RFA) can be considered, due to potential survival benefits especially in case of small tumours (8).